2021
DOI: 10.1063/5.0035539
|View full text |Cite
|
Sign up to set email alerts
|

Solution processable poly(vinylidene fluoride)-based ferroelectric polymers for flexible electronics

Abstract: Since the discovery of piezoelectricity in poly(vinylidene fluoride) (PVDF) 50 years ago, ferroelectric polymers have established their own areas for research and applications due to their unique properties in comparison to single crystals and inorganics. PVDF is a semicrystalline polymer that can crystallize into five different polymorphs. Among them, the polar β-phase is the most interesting one for electroactive properties because it has the highest dipolar moment and the highest piezoelectric response. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…It has been found that organic piezoelectric materials have greater benefits than inorganic materials, including a higher level of processability 16 . Such materials have been seen to be applicable in a wide range of devices, with polymer-based materials being more preferred due to their intrinsic flexible nature, providing a great degree of bending and biodegradability 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that organic piezoelectric materials have greater benefits than inorganic materials, including a higher level of processability 16 . Such materials have been seen to be applicable in a wide range of devices, with polymer-based materials being more preferred due to their intrinsic flexible nature, providing a great degree of bending and biodegradability 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a semi‐crystalline polymer and has five different crystalline phases‐α, β, γ, δ, and ε, of which α and β are the predominant phases. The nonpolar α‐phase (TGTG′ conformation) is the most common and stable polymorph 10–12 . Nevertheless, the polar crystalline β‐phase exists in all‐ trans (TTTT) conformation, which provides the polymer with the largest dipole moment per unit cell, and thus the highest piezoelectric response.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Compared with the rigid and brittle piezoelectric single crystals and ceramics, piezoelectric polymers offer many advantages including lightweight, higher flexibility and much lower dielectric permittivity, which yields a higher piezoelectric voltage constant (e.g., g 33 ) and a higher output voltage when used as a sensor. 10,11 Poly(vinylidene fluoride) (PVDF) is one of the most widely studied and used piezoelectric polymer. It is a semi-crystalline polymer and has five different crystalline phases-α, β, γ, δ, and ε, of which α and β are the predominant phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, polymer-based materials have attained substantial consideration in the fabrication of newer materials for higher appreciable electronics [1], packaging [2], and building applications. Mainly, epoxy resins have gained more interest owing to their better basic and functional properties.…”
Section: Introductionmentioning
confidence: 99%